A Conceptual Study on how Psychometric Instruments are helpful to HRM in Talent Acquisition (Trinity Journal of Management, IT & Media (TJMITM), 2010)
Psychometric tests which otherwise  were once w1 obscure apparatus  are now increasingly becoming a  supportive tool to the Talent  Acquisition process and are  injecting accuracy iflfo the multi• faceted web of HR. These tests that  were earlier ignored due to  complexity are now turning out to  be the DNA of winning  organizations. They aid in the  selection of the 'best human asset'  who can late prove to be the right fit in the organization. It defines the  competency parameters and the  ideal talent to be recruited  according to the designed role. This  gamut of tests measures the thought  processes and aptitude which are  prerequisites for job performance.  It matches people to job and not job  to people. Additionally, it states  acceptance level of the candidate to  n given role. It helps to minimize  subjectivity, nepotism, impulsive  judgements and bias which are a  few of the inherent flaws in the  recruitment process. The tests must  be carefully administered and  interpreted to ensure that only the  'right ' is hired. Nonetheless, the  analyst must be prudent to verify  how long the incumbent would  retain himself with the  organization.
Keywords: Psychometric tests; DNA; Additionally; recruitment process